Oral white sponge naevus: case report - Iamaroon A. (2014)
The clinical appearances of white sponge naevus may mimic other oral white lesions, including premalignant leukoplakia but, unlike leukoplakia, white sponge naevus does not have malignant potential. This article presents a case of an irregular white lesion on the oral mucosa with findings suggestive of white sponge naevus.